Single center study of ESBL-related strains of Enterobacteriaceae collected from clinical specimens of infants with the congenital heart disease using multiplex PCR amplification - Filonenko, G.V.; Talalaiev, O.S.; Kyryk, D.L.; Kovalenko, N.O.; Skorohod, I.M.; Salamanina, A.O. (Вiopolymers and Cell, 2017)
Aim. To study ESBL phenotypes, as well as to identify individual genotypes of β-lactamases and to study their prevalence among clinical strains of Enterobacteriaceae collected from children with the congenital heart disease. Methods. The susceptibility of clinical strains of Enterobacteriaceae to antibiotics was using an automated system; the resistance determinants were genotyped using multiplex PCR. Results. During the period of the study, 10.9 % of ESBL-positive isolates were found among clinical strains of Enterobacteriaceae. Most ESBL-producing strains (33.3 %) were Klebsiella pneumoniae. Most strains producing extended-spectrum β-lactamases were isolated from the respiratory tract and accounted for 83.3 %. Conclusions. This study provided new data on the prevalence of ESBL-producing genetic resistance determinants within the Enterobacteriaceae family and their role in the development of complications. We genotyped ESBL-positive isolates using multiplex PCR. The study demonstrated the diagnostic potential of molecular biology methods in identifying resistance determinants of microorganisms. Мета. Вивчити фенотипи БЛРС і ідентифікацію обраних генотипів β-лактамаз і частоту їх поширення серед клінічних штамів Enterobacteriaceae, виділених у дітей з вродженими вадами серця. Методи. Проведено дослідження клінічних штамів Enterobacteriaceae з метою визначення їх чутливості до антибіотиків з використанням автоматичної системи і з подальшим генотипуванням детермінант резистентності методом мультиплексной ПЛР. Результати. За досліджуваний період серед клінічних штамів Enterobacteriaceae було виявлено 10,9 % БЛРС-позитивних ізолятів. Переважну більшість штамів, продуцентів БЛРС – склали Klebsiella pneumoniae. Найбільша кількість штамів-продуцентів β-лактамаз розширеного спектру дії було виділено з респіраторного тракту і склало 83,3 %. Висновки. Експериментальне дослідження дало нові дані про поширення генетичних детермінант резистентності родини Enterobacteriaceae, що продукують БЛРС і їхню роль у розвитку ускладнень. Робота продемонструвала діагностичну цінність молекулярно-біологічних методів для ідентифікації детермінант резистентності у мікроорганізмів. Цель. Изучить фенотипи БЛРС и идентификацию избранных генотипов β-лактамаз и частоту их распространения среди клинических штаммов Enterobacteriaceae, выделенных у детей с врождёнными пороками сердца. Методы. Проведены исследования клинических штаммов Enterobacteriaceae с целью определения их чувствительности к антибиотикам с использованием автоматической системы и с последующим генотипированием детерминант резистентности методом мультиплексной ПЦР. Результаты. За исследуемый период среди клинических штаммов Enterobacteriaceae было выявлено 10,9 % БЛРС-положительных изолятов. Превалирующее большинство штаммов, продуцентов БЛРС – составили Klebsiella pneumoniae. Наибольшее количество штаммов-продуцентов β-лактамаз расширенного спектра действия было выделено с респираторного тракта и составило 83,3%. Выводы. Экспериментальное исследование дало новые данные о распространении генетических детерминант резистентности в семействе Enterobacteriaceae, которые продуцируют БЛРС и их места в развитии осложнений. Работа продемонстрировала диагностическую ценность молекулярно-биологических методов для идентификации детерминант резистентности у микроорганизмов.